Cloud concrete stone reinforced waste slag light cement foaming wallboard and preparation method thereof

By using cloud concrete stone in the wall panel to reinforce waste slag and industrial waste silk fibers, combined with foaming and foaming technology, a lightweight cement foam wall panel was prepared, which solved the problem of insufficient resource consumption and performance of traditional cement wall panels, and achieved an environmentally friendly, efficient and multifunctional building materials solution.

CN119797839APending Publication Date: 2025-04-11YULIN CHENGTOU GREEN BUILDING TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411980587.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional cement wall panels use a lot of natural resources during the preparation process, resulting in environmental damage and resource depletion. At the same time, they are dense, have high transportation and installation costs, and are single in performance, making it difficult to meet the needs of modern buildings for versatility.

Method used

The lightweight cement foamed wall panel of waste slag is used to reinforce the waste slag lightweight cement, and by rationally utilizing the power plant solid waste slag and industrial waste silk fibers, the material density is reduced and the building performance is improved. The preparation method of this wall panel includes pretreating the foaming agent and the foam stabilizing agent, reasonably proportioning the raw materials, and forming a wall panel with good thermal insulation and sound insulation performance through multi-stage maintenance and molding processes.

Benefits of technology

It effectively reduces dependence and exploitation on natural resources, reduces environmental pollution, realizes the reuse of resources, greatly reduces the density of wall panels, facilitates transportation and installation, and improves the comprehensive performance of thermal insulation and sound insulation, providing users with a more comfortable user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221462340000111
    Figure BDA0005221462340000111
  • Figure BDA0005221462340000112
    Figure BDA0005221462340000112
Patent Text Reader

Abstract

The invention relates to the technical field of wall materials, in particular to a cloud concrete stone reinforced waste slag light cement foaming wallboard and a preparation method thereof.The cloud concrete stone reinforced waste slag light cement foaming wallboard is prepared from, by weight, 34.4%-39.4% of ordinary silicate P.O42.5 R cement, 28.0%-31.6% of I-grade fly ash, 1.0%-3.6% of cloud concrete stone (2-3mm), 10.9%-13.4% of power plant solid waste slag, 0.15%-0.3% of early strength agent and 6.2%-6.6% of foaming agent; the invention relates to an environment-friendly thermal insulation material, which is prepared from the following raw materials in percentage by weight: 0.03%-0.034% of a foam stabilizer, 1.17%-1.22% of a dispersing agent, 0.0047%-0.0073% of a state regulator, 1.35%-1.55% of industrial waste silk fibers and 14.2%-15.9% of water, and is characterized in that wastes such as solid waste furnace slag of a power plant and the industrial waste silk fibers are used, so that the accumulation of the industrial wastes is remarkably reduced, the environmental pollution is effectively reduced, the reutilization of resources is realized, and the environmental pollution is reduced. Through the designed raw material ratio and the preparation process, the density of the wallboard is successfully reduced and is far lower than that of a traditional cement wallboard, the weight of the wallboard is greatly reduced, transportation and installation are facilitated, the comprehensive performance of the wallboard is further improved, and more comfortable use experience is brought to a user.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wall materials, in particular to a cloud concrete stone reinforced waste slag lightweight cement foam wallboard and a preparation method thereof. Background Art

[0002] In the field of building materials, traditional cement wallboards have long dominated. However, with the increasing awareness of environmental protection and the demand for sustainable development, the shortcomings of traditional cement wallboards have gradually become apparent.

[0003] First, traditional cement wallboards often use a large amount of natural resources, such as cement, sand and gravel, in the preparation process. The mining of these resources not only damages the environment, but also faces serious challenges in terms of sustainability as resources become increasingly depleted. In addition, the high density of traditional cement wallboards leads to high transportation and installation costs, which is not conducive to energy conservation and emission reduction in the construction industry.

[0004] Secondly, the performance of traditional cement wall panels is relatively single, and it is difficult to meet the multifunctional needs of modern buildings. For example, in terms of thermal insulation and sound insulation, the performance of traditional cement wall panels is often unsatisfactory, which not only affects the comfort of the building, but also increases the energy consumption of the building.

[0005] Therefore, it is necessary to develop a new type of building material to overcome the above-mentioned shortcomings of traditional cement wall panels. The development of Yuntongshi reinforced waste slag lightweight cement foam wall panels is based on this demand. It aims to provide a more environmentally friendly, efficient and multifunctional solution for the field of building materials by rationally utilizing industrial waste, reducing material density and improving building performance. Summary of the invention

[0006] Technical issues solved

[0007] In view of the above-mentioned shortcomings of the prior art, the present invention provides a cloud concrete stone reinforced waste slag lightweight cement foam wall panel and a preparation method thereof. The present invention uses waste materials such as power plant solid waste slag and industrial waste silk fiber. This raw material selection not only significantly reduces the accumulation of industrial waste, effectively reduces environmental pollution, but also realizes the recycling of resources. After proper treatment, the power plant slag can replace part of the traditional materials and become one of the main raw materials for the wall panel, thereby effectively reducing the dependence on and exploitation of natural resources. At the same time, through carefully designed raw material ratios and foaming preparation processes, the present invention successfully reduces the density of the wall panel, making it much lower than that of traditional cement wall panels, which not only greatly reduces the weight of the wall panel and facilitates transportation and installation, but also further improves the comprehensive performance of the wall panel, such as thermal insulation and sound insulation, bringing users a more comfortable use experience.

[0008] Technical Solution

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] On the one hand, a cloud concrete stone reinforced waste slag lightweight cement foam wallboard includes the following raw materials in weight percentage: ordinary silicate P.O42.5R cement 34.4%-39.4%, grade I fly ash 28.0%-31.6%, cloud concrete stone (2-3mm) 1.0%-3.6%, power plant solid waste slag 10.9%-13.4%, early strength agent 0.15-0.3%, foaming agent 6.2%-6.6%, foam stabilizer 0.03%-0.034%, dispersant 1.17%-1.22%, state regulator 0.0047%-0.0073%, industrial waste silk fiber 1.35%-1.55%, and water 14.2%-15.9%.

[0011] Furthermore, the foaming agent has two raw materials, thick and thin, which are used after being diluted according to the ratio of thick: thin: water = 0.5:0.5: (31-33).

[0012] Furthermore, the state regulator is diluted with water at a ratio of (0.8-1.2):200, the dispersant and the diluted regulator are diluted with water at a ratio of 1:5 before use, and the foam stabilizer is diluted with water at a ratio of 1:15 before use after stirring and dissolving.

[0013] Furthermore, the specific surface area of ​​the ordinary silicate P.O42.5R cement is 300-350m 2 / kg.

[0014] Furthermore, the fineness of the Class I fly ash is 12%-20% (45 μm square hole sieve residue).

[0015] Furthermore, the particle shape of the cloud concrete stone (2-3 mm) is spherical or approximately spherical, and the cylinder compressive strength of the cloud concrete stone is 10-15 MPa.

[0016] Furthermore, the particle size of the power plant slag is 5-16 mm, the foam stabilizer is cellulose: polyvinyl alcohol = 2:1, the prepared foam stabilizer is then added to water at a ratio of 1:15 and stirred to dissolve, and the early strength agent is calcium formate.

[0017] Furthermore, the length of the industrial waste silk fiber is 30-50 mm, and the industrial waste silk fiber is polyester fiber.

[0018] On the other hand, the preparation method of the waste slag lightweight cement foam wallboard reinforced with cloud concrete stone is characterized by comprising the following steps:

[0019] S100, pretreatment of the foaming agent: diluting the thick and thin raw materials of the foaming agent according to the ratio of thick: thin: water = 0.5:0.5:(31-33), and then sending the diluted foaming agent into a batching tank for standby use;

[0020] S200, state regulator, dispersant and foam stabilizer pretreatment: first dilute the state regulator with water at a ratio of (0.8-1.2):200, then dilute the dispersant and the diluted state regulator at a ratio of 1:5, and then send the materials into the batching tank for standby use, and dilute the foam stabilizer with water at a ratio of 1:15, stir and dissolve for standby use;

[0021] S300, upper mixer mixing ingredients:

[0022] Start the upper mixer, first mix 14.2%-15.9% water and 1.17%-1.22% dispersant and stir for 10 seconds to ensure that the water and dispersant are fully mixed and the dispersant is evenly dispersed in the water, creating good conditions for subsequent raw material mixing;

[0023] Then, 34.4%-39.4% of ordinary silicate P.O42.5R cement and 28.0%-31.6% of Class I fly ash are mixed and stirred for 50 seconds. Under the action of dispersant and water, cement and fly ash are fully mixed, and a preliminary hydration reaction begins to form a slurry with a certain viscosity.

[0024] S400, lower mixer mixing ingredients:

[0025] The slurry after stirring in the upper layer is unloaded into the mixer in the lower layer, and the stirring in the lower layer is started;

[0026] First add 0.15-0.3% early strength agent to accelerate the hydration reaction of cement and make the slurry gain early strength faster;

[0027] Then add 1.35%-1.55% of industrial waste silk fiber and stir for 15 seconds, so that the industrial waste silk fiber is evenly distributed in the slurry to enhance the toughness of the slurry;

[0028] Then add 0.03%-0.034% of the foam stabilizer to water at a ratio of 1:15 and stir to dissolve, then add the material and stir for 60 seconds to ensure that the foam stabilizer fully plays the role of stabilizing bubbles and ensures the stability of bubbles in the slurry;

[0029] S500, other raw materials added and stirred:

[0030] Add 1.0%-3.6% of cloud concrete stone (2-3mm) and 10.9%-13.4% of power plant slag. After adding the materials, stir for 5 seconds and then stop. The addition of cloud concrete stone and power plant slag further fills and enhances the volume stability of the slurry and enhances the shrinkage resistance of the formed wallboard.

[0031] Add 6.2%-6.6% of foaming agent and start stirring at the same time. Continue stirring for 20 seconds after adding the foaming agent. The foaming agent is added at this time to generate a large number of bubbles in the slurry, forming a foamed lightweight slurry structure;

[0032] S600, curing and molding:

[0033] The slurry pouring mold car, after vibration debubbling and secondary leveling, enters the primary curing kiln (temperature 45℃) for curing for 2 hours. The vibration debubbling and secondary leveling operations make the bubbles in the slurry more evenly distributed. The curing in the primary curing kiln allows the wallboard to initially gain strength.

[0034] After leaving the kiln, it is pressed into shape, then put into the secondary curing kiln (temperature 50℃) for curing for 2-3 hours, and then put into the tertiary curing kiln (temperature 50℃) for curing for 2-3 hours. The multi-stage curing further improves the strength and performance of the wallboard;

[0035] The surface is cleaned by the machine, the board is demoulded and put into the autoclave for curing at 90℃ for 8 hours, and the finished products are packaged and stacked for storage.

[0036] Beneficial Effects

[0037] Compared with the known public technology, the technical solution provided by the present invention has the following advantages:

[0038] Beneficial effects:

[0039] In the preparation process of the cloud concrete stone reinforced waste slag lightweight cement foam wallboard in the present invention, wastes such as power plant solid waste slag and industrial waste silk fiber are used. This raw material selection not only helps to reduce the accumulation of industrial waste and reduce environmental pollution, but also realizes the recycling of resources. Power plant slag, as industrial waste, can be used as one of the main raw materials for wallboards after proper treatment, replacing some traditional materials, thereby reducing the exploitation of natural resources. At the same time, the utilization of industrial waste silk fiber also reduces the generation of waste in the textile industry, providing a new way for the resource utilization of waste.

[0040] Through reasonable raw material ratio and preparation process, the density of the wallboard of the present invention is effectively controlled, which is much lower than the density of traditional cement wallboards, which makes the wallboard more convenient in transportation and installation. At the same time, the compressive strength of the wallboard also reaches a relatively high level, which can meet the strength requirements of the building structure. In addition, the wallboard also has good thermal insulation and sound insulation properties, which helps to improve the thermal insulation effect and sound insulation performance of the building and provide a more comfortable living environment for residents. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The present invention will be further described below in conjunction with the embodiments.

[0043] Example 1: Preparation and performance testing of lightweight cement foamed wallboard reinforced with waste slag using cloud concrete stone

[0044] 1. Raw material preparation:

[0045] The specific surface area is 300m 2 / kg of ordinary silicate P.O42.5R cement, the dosage is 34.4% (calculated based on the total weight of raw materials of 2049kg, i.e. 705kg).

[0046] Select Class I fly ash with a fineness of 12% (45 μm square hole sieve residue) and use an amount of 31.6% (647 kg).

[0047] Cloud concrete stone (2-3mm), spherical particle shape, cylinder pressure strength of 10MPa, dosage accounts for 1.0% (20kg).

[0048] Power plant slag with a particle size of 5 mm accounts for 13.4% (275 kg) of the total weight of raw materials.

[0049] Calcium formate is used as an early strength agent in an amount of 0.15% (3 kg).

[0050] The foaming agent is diluted according to the ratio of thick: thin: water = 0.5:0.5:31 and the usage is 6.2% (127kg).

[0051] Cellulose: polyvinyl alcohol = 2:1, add water at a ratio of 1:15 and stir to dissolve as a foam stabilizer, with a dosage of 0.03% (0.662 kg).

[0052] The state regulator is diluted with water at a ratio of 0.8:200 before use, and the content is 0.0047% (0.096kg).

[0053] The dispersant and the diluted state regulator are diluted at a ratio of 1:5, and the dosage is 1.17% (24.0 kg).

[0054] Polyester fibers with a length of 30 mm were used as industrial waste silk fibers, and the amount used was 1.35% (27.7 kg).

[0055] The water usage accounted for 14.2% (290 kg).

[0056] 2. Raw material pretreatment:

[0057] Foaming agent pretreatment:

[0058] Take 50kg of thick foaming agent and 50kg of thin foaming agent, add 3100kg of water to dilute, and then put them into the batching tank for use.

[0059] Conditioner and dispersant pretreatment:

[0060] Take 4 kg of state regulator, add 1000 kg of water to dilute, then take 200 kg of dispersant and dilute with the diluted 1000 kg of state regulator at a ratio of 1:5, mix and send into the batching tank for standby use.

[0061] Foam stabilizer pretreatment:

[0062] The foam stabilizer is prepared according to the ratio of cellulose to polyvinyl alcohol = 2:1. Take 0.662 kg of the foam stabilizer, add 10 kg of water and stir quickly with a stirrer. After it dissolves, use it as the foam stabilizer for later use.

[0063] 3. Mixing process:

[0064] Mixing ingredients in the upper mixer:

[0065] Start the upper mixer, add 280kg water and 24kg dispersant and stir for 10 seconds, then add 705kg cement and 647kg fly ash and stir for 50 seconds.

[0066] The lower mixer mixes the ingredients:

[0067] After stirring the upper layer, the slurry is unloaded into the lower mixer, and the state and fluidity of the slurry are observed. According to the state and fluidity, the water consumption and dispersant dosage of the second batch of slurry are appropriately adjusted. Start stirring the lower layer, first add 3kg of early strength agent and stir for 30 seconds, then add 27.7kg of industrial waste silk fiber and stir for 15 seconds, and then add 0.662kg of dissolved foam stabilizer and stir for another 60 seconds.

[0068] Add other ingredients and stir:

[0069] Add 20kg of cloud concrete stone and 223kg of solid waste slag from the power plant, stir for 5 seconds after adding the materials, then stop the machine, then add 127kg of foaming agent and start stirring at the same time, after adding the foaming agent, continue stirring for 20 seconds before stopping and discharging.

[0070] 4. Curing and molding:

[0071] The slurry pouring mold car, after vibration to remove bubbles and secondary flattening, enters the first-level curing kiln (temperature 45℃) for curing for 2 hours. After leaving the kiln, it is pressed into shape, and then enters the second-level curing kiln (temperature 50℃) for curing for 3 hours, and then enters the third-level curing kiln (temperature 50℃) for curing for 3 hours. Finally, it passes through the cleaning machine, demoulds and takes out the board, and enters the autoclave for curing at 90℃ for 8 hours. The finished products are packaged, stacked and put into storage.

[0072] 5. Performance test results:

[0073] The measured density is about 840kg / m 3The compressive strength is 6.5MPa, the heat transfer coefficient is 0.1W / (㎡·K), and the sound insulation performance is 42dB.

[0074] Example 2: Adjusting the raw material ratio of cloud concrete stone to reinforce the waste slag lightweight cement foam wallboard

[0075] 1. Raw material preparation:

[0076] The specific surface area is 320m 2 / kg of ordinary silicate P.O42.5R cement, the dosage is 36.4% (745kg).

[0077] The usage of Class I fly ash with a fineness of 13% (45μm square hole sieve residue) is 30.2% (619kg).

[0078] Cloud concrete stone (2-3mm), spherical, cylinder pressure strength is 12MPa, the dosage is 2% (40kg).

[0079] Huadian slag with a particle size of 10 mm accounts for 12.4% (254 kg).

[0080] Calcium formate early strength agent, dosage is 0.25% (5.1kg).

[0081] The foaming agent is diluted according to the ratio of thick: thin: water = 0.5:0.5:32 and the usage is 6.4% (132kg).

[0082] Cellulose: polyvinyl alcohol = 2:1, add water at a ratio of 1:15, stir and dissolve as a foam stabilizer, the dosage is 0.033% (0.676kg).

[0083] The state regulator is diluted with water at a ratio of 1:200 before use, and the content is 0.006% (0.122kg).

[0084] The dispersant and the diluted state regulator are diluted at a ratio of 1:5, and the dosage is 1.2% (24.5 kg).

[0085] Polyester fibers with a length of 40 mm were used as industrial waste silk fibers, and the amount used was 1.45% (29.7 kg).

[0086] The water usage accounted for 15.2% (311 kg).

[0087] 2. Raw material pretreatment:

[0088] Foaming agent pretreatment:

[0089] Take 50kg of thick foaming agent and 50kg of thin foaming agent, add 3200kg of water to dilute, and then put them into the batching tank for standby use.

[0090] Conditioner and dispersant pretreatment:

[0091] Take 5kg of state regulator, add 1000kg of water to dilute, then take 200kg of dispersant and dilute with the diluted 1000kg of state regulator at a ratio of 1:5, mix and send into the batching tank for standby use.

[0092] Foam stabilizer pretreatment:

[0093] The foam stabilizer is prepared according to the ratio of cellulose to polyvinyl alcohol = 2:1. Take 0.676 kg of the foam stabilizer, add 10 kg of water and stir quickly with a stirrer. After it dissolves, use it as the foam stabilizer for later use.

[0094] 3. Mixing process:

[0095] Mixing ingredients in the upper mixer:

[0096] Start the upper mixer, add 311kg water and 24.5kg dispersant and stir for 10 seconds, then add 745kg cement and 619kg fly ash and stir for 50 seconds.

[0097] The lower mixer mixes the ingredients:

[0098] After stirring the upper layer, the slurry is unloaded into the lower mixer. The state and fluidity of the slurry are observed, and the water consumption and dispersant dosage of the second batch of slurry are fine-tuned according to the state and fluidity. The lower layer stirring is started, and 5.1 kg of early strength agent is added and stirred for 30 seconds, then 29.7 kg of industrial waste silk fiber is added and stirred for 15 seconds, and then 0.676 kg of dissolved foam stabilizer is added and stirred for 60 seconds.

[0099] Add other ingredients and stir:

[0100] Add 40kg of cloud concrete stone and 245kg of solid waste slag from the power plant, stir for 5 seconds after adding the materials, then stop the machine, then add 132kg of foaming agent and start stirring at the same time, after adding the foaming agent, continue stirring for 20 seconds before stopping and discharging.

[0101] 4. Curing and molding:

[0102] The slurry pouring mold car, after vibration to remove bubbles and secondary flattening, enters the first-level curing kiln (temperature 45℃) for curing for 2 hours. After leaving the kiln, it is pressed into shape, and then enters the second-level curing kiln (temperature 50℃) for curing for 3 hours, and then enters the third-level curing kiln (temperature 50℃) for curing for 3 hours. Finally, it passes through the cleaning machine, demoulds and takes out the board, and enters the autoclave for curing at 90℃ for 8 hours. The finished products are packaged, stacked and put into storage.

[0103] 5. Performance test results:

[0104] Density is about 850kg / m 3 , compressive strength is 7.0MPa, heat transfer coefficient is 0.12W / (m·K), and sound insulation performance is 43dB.

[0105] Example 3: Further adjustment of raw material ratio

[0106] 1. Raw material preparation:

[0107] The specific surface area is 350m 2 / kg of ordinary silicate P.O42.5R cement, the dosage is 39.4% (807kg).

[0108] The usage of Class I fly ash with a fineness of 15% (45μm square hole sieve residue) is 28.0% (574kg).

[0109] Cloud concrete stone (2-3mm), spherical, cylinder pressure strength is 15MPa, the dosage accounts for 3.6% (74kg).

[0110] Power plant slag with a particle size of 16 mm accounts for 10.9% (223 kg).

[0111] Calcium formate early strength agent, dosage is 0.3% (6.1kg).

[0112] The foaming agent is diluted according to the ratio of thick: thin: water = 0.5:0.5:33, and the dosage is 6.6% (136kg)

[0113] Cellulose: polyvinyl alcohol = 2:1, add water at a ratio of 1:15, stir and dissolve as a foam stabilizer, the dosage is 0.034% (0.697kg).

[0114] The state regulator is diluted with water at a ratio of 1.2:200 before use, and the content is 0.0073% (0.15kg).

[0115] The dispersant and the diluted state regulator are diluted at a ratio of 1:5, and the dosage is 1.22% (25.0 kg).

[0116] Polyester fibers with a length of 50 mm were used as industrial waste silk fibers, and the amount used was 1.55% (31.7 kg).

[0117] The water usage accounted for 15.9% (325 kg).

[0118] 2. Raw material pretreatment:

[0119] Foaming agent pretreatment:

[0120] Take 50kg of thick foaming agent and 50kg of thin foaming agent, add 3300kg of water to dilute, and then send them into the batching tank for standby use.

[0121] Conditioner and dispersant pretreatment:

[0122] Take 6 kg of state regulator, add 1000 kg of water to dilute, then take 200 kg of dispersant and dilute with the diluted 1000 kg of state regulator at a ratio of 1:5, mix and send into the batching tank for standby use.

[0123] Foam stabilizer pretreatment:

[0124] The foam stabilizer is prepared according to the ratio of cellulose to polyvinyl alcohol = 2:1. Take 0.697 kg of the foam stabilizer, add 10 kg of water and stir quickly with a stirrer. After it dissolves, use it as the foam stabilizer for later use.

[0125] 3. Mixing process:

[0126] Mixing ingredients in upper mixer:

[0127] Start the upper mixer, add 325kg water and 25.0kg dispersant and stir for 10 seconds, then add 807kg cement and 574kg fly ash and stir for 50 seconds.

[0128] The lower mixer mixes the ingredients:

[0129] After stirring the upper layer, the slurry is unloaded into the lower mixer. The state and fluidity of the slurry are observed, and the water consumption and dispersant dosage of the second batch of slurry are fine-tuned according to the state and fluidity. Start stirring the lower layer, first add 6.1kg of early strength agent and stir for 30 seconds, then add 31.7kg of industrial waste silk fiber and stir for 15 seconds, and then add 0.697kg of dissolved foam stabilizer and stir for 60 seconds.

[0130] Add other ingredients and stir:

[0131] 74kg of cloud concrete stone and 223kg of solid waste slag from the power plant were added, and after adding the materials, the machine was stirred for 5 seconds and then stopped. Then, 136kg of foaming agent was added and stirring was started at the same time. After the foaming agent was added, stirring was continued for 20 seconds before stopping and discharging.

[0132] 4. Curing and molding:

[0133] The slurry pouring mold car, after vibration to remove bubbles and secondary flattening, enters the first-level curing kiln (temperature 45℃) for curing for 2 hours. After leaving the kiln, it is pressed into shape, and then enters the second-level curing kiln (temperature 50℃) for curing for 3 hours, and then enters the third-level curing kiln (temperature 50℃) for curing for 3 hours. Finally, it passes through the cleaning machine, demoulds and takes out the board, and enters the autoclave for curing at 90℃ for 8 hours. The finished products are packaged, stacked and put into storage.

[0134] 5. Performance test results:

[0135] Density is about 860kg / m 3 , compressive strength is 7.3MPa, thermal conductivity is 0.14W / (m·K), and sound insulation performance is 44dB.

[0136] Comparative Example 1: Traditional Cement Wallboard

[0137] 1. Raw materials and preparation:

[0138] Ordinary Portland cement is used to prepare cement wall panels according to traditional processes, without adding special raw materials such as cloud concrete stone, power plant slag, and foaming agent.

[0139] 2. Performance test results:

[0140] The measured density is about 2000kg / m 3 , compressive strength is 10MPa, thermal conductivity is 1.0W / (m·K), and sound insulation performance is 30dB.

[0141] Comparison of wallboard performance with different raw material ratios (taking different cloud concrete stone contents as an example):

[0142]

[0143] Compared with traditional cement wall panels:

[0144]

[0145] It can be seen from the above embodiments and comparative examples that the cloud concrete stone reinforced waste slag lightweight cement foam wallboard has obvious advantages over the traditional cement wallboard in terms of density, thermal insulation, sound insulation and other properties, and its own performance can be further optimized by adjusting the raw material ratio.

[0146] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A lightweight cement foam wallboard reinforced with waste slag using cloud concrete stone, characterized in that: The invention comprises the following raw materials in weight percentage: 34.4%-39.4% of ordinary silicate P.O42.5R cement, 28.0%-31.6% of grade I fly ash, 1.0%-3.6% of cloud concrete stone (2-3mm), 10.9%-13.4% of solid waste slag from power plant, 0.15%-0.3% of early strength agent, 6.2%-6.6% of foaming agent, 0.03%-0.034% of foam stabilizer, 1.17%-1.22% of dispersant, 0.0047%-0.0073% of state regulator, 1.35%-1.55% of industrial waste silk fiber and 14.2%-15.9% of water.

2. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The foaming agent has two raw materials, thick and thin, which are used after being diluted according to the ratio of thick: thin: water = 0.5:0.5: (31-33).

3. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The state regulator is diluted with water at a ratio of (0.8-1.2):200, and the dispersant and the diluted regulator are diluted at a ratio of 1:5 before use.

4. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The specific surface area of ​​the ordinary silicate P.O42.5R cement is 300-350m 2 / kg.

5. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The fineness of the Class I fly ash is 12%-20% (residue on a 45 μm square hole sieve).

6. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The particle shape of the cloud concrete stone (2-3 mm) is spherical or approximately spherical, and the cylinder compressive strength of the cloud concrete stone is 10-15 MPa.

7. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The particle size of the power plant slag is 5-16 mm, the foam stabilizer is cellulose: polyvinyl alcohol = 2:1, the prepared foam stabilizer is added with water at a ratio of 1:15 and stirred to dissolve, and the early strength agent is calcium formate.

8. The cloud concrete stone reinforced waste slag lightweight cement foam wallboard according to claim 1, characterized in that: The length of the industrial waste silk fiber is 30-50 mm, and the industrial waste silk fiber is polyester fiber.

9. The method for preparing the waste slag lightweight cement foam wallboard reinforced with cloud concrete stone according to any one of claims 1 to 8, characterized in that: The following steps are involved: S100, pretreatment of the foaming agent: diluting the thick and thin raw materials of the foaming agent according to the ratio of thick: thin: water = 0.5:0.5:(31-33), and then sending the diluted foaming agent into a batching tank for standby use; S200, state regulator, dispersant and foam stabilizer pretreatment: first dilute the state regulator with water at a ratio of (0.8-1.2):200, then dilute the dispersant and the diluted state regulator at a ratio of 1:5, and then send the materials into the batching tank for standby use, and dilute the foam stabilizer with water at a ratio of 1:15, stir and dissolve for standby use; S300, upper mixer mixing ingredients: Start the upper mixer, first mix 14.2%-15.9% water and 1.17%-1.22% dispersant and stir for 10 seconds to ensure that the water and dispersant are fully mixed and the dispersant is evenly dispersed in the water, creating good conditions for subsequent raw material mixing; Then, 34.4%-39.4% of ordinary silicate P.O42.5R cement and 28.0%-31.6% of Class I fly ash are mixed and stirred for 50 seconds. Under the action of dispersant and water, cement and fly ash are fully mixed, and a preliminary hydration reaction begins to form a slurry with a certain viscosity. S400, lower mixer mixing ingredients: The slurry after stirring in the upper layer is unloaded into the mixer in the lower layer, and the stirring in the lower layer is started; First add 0.15%-0.3% early strength agent to accelerate the hydration reaction of cement and make the slurry gain early strength faster; Then add 1.35%-1.55% of industrial waste silk fiber and stir for 15 seconds, so that the industrial waste silk fiber is evenly distributed in the slurry to enhance the toughness of the slurry; Then add 0.03%-0.034% of the foam stabilizer and dissolve it in water at a ratio of 1:15, add the materials and stir for 60 seconds to ensure that the foam stabilizer can fully play its role in stabilizing bubbles and ensure the stability of bubbles in the slurry; S500, other raw materials added and stirred: Add 1.0%-3.6% of cloud concrete stone (2-3mm) and 10.9%-13.4% of power plant slag. After adding the materials, stir for 5 seconds and then stop. The addition of cloud concrete stone and power plant slag further fills and enhances the volume stability of the slurry and enhances the shrinkage resistance of the formed wallboard. Add 6.2%-6.6% of foaming agent and start stirring at the same time. Continue stirring for 20 seconds after adding the foaming agent. The foaming agent is added at this time to generate a large number of bubbles in the slurry, forming a foamed lightweight slurry structure; S600, curing and molding: The slurry pouring mold car, after vibration debubbling and secondary leveling, enters the primary curing kiln (temperature 45℃) for curing for 2 hours. The vibration debubbling and secondary leveling operations make the bubbles in the slurry more evenly distributed. The curing in the primary curing kiln allows the wallboard to initially gain strength. After leaving the kiln, it is pressed into shape, then put into the secondary curing kiln (temperature 50℃) for curing for 2-3 hours, and then put into the tertiary curing kiln (temperature 50℃) for curing for 2-3 hours. The multi-stage curing further improves the strength and performance of the wallboard; The surface is cleaned by the machine, the board is demoulded and put into the autoclave for curing at 90℃ for 8 hours, and the finished products are packaged and stacked for storage.